Spinal Cord Stimulation Exerts Neuroprotective Effects against Experimental Parkinson’s Disease - Shinko, Aiko (Public Library of Science, 2014)
In clinical practice, deep brain stimulation (DBS) is effective for treatment of motor symptoms in Parkinson’s disease (PD). However, the mechanisms have not been understood completely. There are some reports that electrical stimulation exerts neuroprotective effects on the central nervous system diseases including cerebral ischemia, head trauma, epilepsy and PD, although there are a few reports on neuroprotective effects of spinal cord stimulation (SCS). We investigated the neuroprotective effects of high cervical SCS on PD model of rats. Adult female Sprague-Dawley rats received hour-long SCS (2, 50 or 200 Hz) with an epidural electrode at C1–2 level for 16 consecutive days. At 2 days after initial SCS, 6-hydroxydopamine (6-OHDA) was injected into the right striatum of rats. Behavioral evaluations of PD symptoms were employed, including cylinder test and amphetamine-induced rotation test performed at 1 and 2 weeks after 6-OHDA injection. Animals were subsequently euthanized for immunohistochemical investigations. In order to explore neurotrophic and growth factor upregulation induced by SCS, another cohort of rats that received 50 Hz SCS was euthanized at 1 and 2 weeks after lesion for protein assays. Behavioral tests revealed that the number of amphetamine-induced rotations decreased in SCS groups. Immunohistochemically, tyrosine hydroxylase (TH)-positive fibers in the striatum were significantly preserved in SCS groups. TH-positive neurons in the substantia nigra pars compacta were significantly preserved in 50 Hz SCS group. The level of vascular endothelial growth factor (VEGF) was upregulated by SCS at 1 week after the lesion. These results suggest that high cervical SCS exerts neuroprotection in PD model of rats, at least partially by upregulation of VEGF. SCS is supposed to suppress or delay PD progression and might become a less invasive option for PD patients, although further preclinical and clinical investigations are needed to confirm the effectiveness and safety.